2012
DOI: 10.1007/s00705-012-1340-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of rabbit hemorrhagic disease virus in China and the antigenic variation of new strains

Abstract: This study aimed to investigate rabbit hemorrhagic disease virus (RHDV) in China. VP60 sequences of five RHDVs collected by our team, as well as those of 16 other published Chinese RHDV strains, were analyzed. Polygenic analysis using MEGA 4 software showed that 20 of the 21 Chinese strains could be clustered in the RHDVa subgroup, and WX/China/1984 was different from them. The Chinese RHDV strains were further classified into four subgroups, CH1 to CH4. Subgroup CH1, represented by the WX/China/1984 strain, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
4
26
0
Order By: Relevance
“…There are indications that members of the RHDVa subgroup of RHDV, which are antigenically distinct to classical RHDV strains like the v351 strain, are replacing the classical RHDV strains in both farmed and wild rabbits in some Asian and European countries [9,24-27]. RHDVa has so far not been described in wild populations from the Iberian Peninsula [28-31].…”
Section: Introductionmentioning
confidence: 99%
“…There are indications that members of the RHDVa subgroup of RHDV, which are antigenically distinct to classical RHDV strains like the v351 strain, are replacing the classical RHDV strains in both farmed and wild rabbits in some Asian and European countries [9,24-27]. RHDVa has so far not been described in wild populations from the Iberian Peninsula [28-31].…”
Section: Introductionmentioning
confidence: 99%
“…The subclusters in the distinct RHDV groups have been termed genogroups 1-6 (G1-G6) (Le Gall-ReculĂ© et al, 2003Le Gall et al, 1998;Nyström et al, 2011;Wang et al, 2012). The G6 cluster is also referred to as RHDVa (Capucci et al, 1998), while the RHDVb branch is also identified as RHDV2 (Dalton et al, 2012;Le Gall-ReculĂ© et al, 2013;Puggioni et al, 2013 In order to confirm whether these epitopes contribute to HBGA binding, we performed synthetic oligosaccharidebased binding assays and mAb blocking assays.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses and the study on phylodynamics of RHDV strains has been the subject of many publications [2,3,5,[7][8][9][11][12][13][14][15][16][18][19][20][22][23][24][25][28][29][30]. The analyses performed indicate that RHDV strains are grouped depending on the time of strain isolation and on geographic location, and that the strains referred to as antigen variants RHDVa (new RHDVa subtype) are genetically distanced from the strains referred to as original RHDV subtype, which is manifested by formation of completely separate genetic groups.…”
Section: Introductionmentioning
confidence: 99%